Correlation of Physician-Assessed Psoriasis Area and Severity Index Scores With Patient-Reported Psoriasis Symptoms and Signs Diary Scores Among Patients With Moderate-to-Severe Psoriasis: Results From VOYAGE 1 and VOYAGE 2 Studies. Issue 3 (July 2019) - Gordon, Kenneth B.; Han, Chenglong; Li, Shu; You, Yin; Song, Michael; Fakharzadeh, Steven; Crowley, Jeffrey J.; Reich, Kristian
Background: Patient-reported and clinician-determined outcomes do not always correlate in clinical trials for psoriasis, even among those with clear skin. Objective: To compare clinical responses with patient-reported outcomes among patients with psoriasis enrolled in 2 phase 3, double-blind, controlled trials of guselkumab (VOYAGE 1 and VOYAGE 2). Methods: Overall, 1432 patients randomized to guselkumab, placebo, or adalimumab at baseline were included in the pooled patient population; measures were assessed at baseline and week 16. End points included proportions of patients achieving 100% improvement in their Psoriasis Area and Severity Index (PASI 100) score and summary scores = 0 on the Psoriasis Symptoms and Signs Diary (PSSD). Proportions of patients with PSSD symptom/sign summary scores = 0 and mean PSSD summary scores were summarized by PASI 100 status. Association between PASI and PSSD scores were evaluated using Pearson correlation coefficients. Results: Among week-16 PASI 100 responders, 46.8% and 34.1% reported PSSD symptom and sign summary scores = 0, respectively, and 30.9% and 49.0% reported minimal symptoms/signs (scores = 1 to <10), respectively; mean scores (scale 0-100) were 6.4 for symptoms and 5.8 for signs. Among PASI 100 nonresponders, only 11.1% (symptoms) and 7.5% (signs) reported PSSD summary scores = 0; mean scores were 25.7 and 26.7, respectively. Correlation coefficients between overall PASI response and PSSD scores were 0.63 (symptoms) and 0.68 (signs; both P < .0001). Conclusion: While PASI and PSSD scores were highly correlated and most PASI 100 responders reported no/minimal symptoms or signs at week 16, substantial discrepancies were found between complete clearance from the clinician's view versus symptom/sign-free status from patients' perspectives.